EXPERT SYSTEM TO DIAGNOSE DISEASES IN THE HUMAN DIGESTIVE SYSTEM USING THE FORWARD CHAINING METHOD CASE STUDY OF PUSKESMAS HUTAGODANG HEALTH CENTER - Daulay, Siti Aisyah; Subagio, S; Ritonga, Wahyu Azhar (U-NET Jurnal Teknik Informatika, 2024)
The era that is increasingly developing requires that we have to keep up with the times that are increasingly developing. Meant in medical science, in detecting disease must also follow the current developments. Digestion is one of the organs that exist in humans created by God. The digestive system is present in the body, it is difficult to detect any disease that is in the digestive tract. With this expert system, it is able to make it easier to detect digestive diseases with the help of information technology. And the data makes it easier for medicine to detect this disease. By making applications using WEB, with MySQL and XAmpp databases. By using the Forward Chaining method.